Cancer related fatigue among patients with lung cancer - Kruk, Agnieszka; Książek, Janina (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Introduction. Lung cancer is one of the most common neoplasm in the world. One of the main ailment connected with neoplasm is fatigue. Statistics show that fatigue is related to over 70% cancer patients. Because of insufficient knowledge about cancer related fatigue it is often ignored in a treatment and care plan what affects quality of provided care and quality of life cancer patients. Aim. The main aim of the study is to estimate a fatigue level among patients with lung cancer in preoperative stage. Estimation criterions comprised: general fatigue, physical fatigue, decreased activity, decreased motivation, psychic fatigue. Material and methods. Research has been conducted in the group of 100 patients of Thoracosurgery Clinic of Medical University of Gdansk qualified for operation because of lung cancer. To estimate fatigue level used a statistical analysis and a method of diagnostic poll with using a MFI-20 form. Results and conclusions. Results show that fatigue is one of the most common disorder among patients with lung cancer. Patients indicated physical fatigue and general fatigue as the most disturbing. What is more research showed that the level of fatigue is connected to the period of hospitalization. Due to this fact has been proved that operation can cause dynamic changes in perceiving fatigue and decreasing motivation to treatment among patients with lung cancer.